TRANSFORMASI KARAKTERISTIK TANAH SAWAH PADA LAHAN BEKAS PENAMBANGAN EMAS DI KABUPATEN SIJUNJUNG SUMATERA BARAT - Elsa Lolita Putri; G Gusmini; A Adrinal; Y Yaherwandi (Jurnal Tanah dan Sumberdaya Lahan, 2021)
The process of physical and chemical properties of the former gold mining soil which is caused by the transformation of different land conditions in natural rice fields, reclaimed rice fields, and mine fields. This study aims to determine the differences in the characteristics of the former gold mining soil in natural rice fields, reclaimed rice fields and mining fields in Sijunjung Regency. There were three sampling locations with three sample points each and the samples were analyzed physically and chemically. Results of this study showed that natural paddy soil has optimal conditions for the growth of rice plants followed by reclaimed lowland soil and the worst was in mining paddy soil based on soil physical and chemical properties. The difference in soil physical properties in the form of natural paddy soil texture was smoother compared to land conditions in reclaimed rice fields and mining rice fields. This was due to intensive inundation processes, which created a plough tread layer, low volume weight accompanied by a moderate total pore space. The difference in chemical properties was in the stable pH of natural paddy soil due to inundation and high organic carbon accompanied by rice reclamation and very low organic carbon in mining soils, which would affect the growth of rice plant.